2023
DOI: 10.3390/biomedicines11020375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH, Ionic Strength and Agitation Rate on Dissolution Behaviour of 3D-Printed Tablets, Tablets Prepared from Ground Hot-Melt Extruded Filaments and Physical Mixtures

Abstract: With the current focus on 3D-printing technologies, it is essential to understand the processes involved in such printing methods and approaches to minimize the variability in dissolution behaviour to achieve better quality control outcomes. For this purpose, two formulations of theophylline tablets were prepared using hydroxypropyl cellulose (HPC) and ethyl cellulose (EC). Among the two types of tablets, three different methods (physical mixture (PM), hot-melt extrusion (HME) and 3D-printing fused deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The dissolution and release of a drug are pivotal factors influencing its absorption and bioavailability, thereby playing a crucial role in drug efficacy and toxicity ( Raman et al, 2023 ; Nashed et al, 2023 ). In our investigation of albendazole, we focused on evaluating the dissolution rate of albendazole solid dispersion and its physical mixture in simulated gastric fluid.…”
Section: Resultsmentioning
confidence: 99%
“…The dissolution and release of a drug are pivotal factors influencing its absorption and bioavailability, thereby playing a crucial role in drug efficacy and toxicity ( Raman et al, 2023 ; Nashed et al, 2023 ). In our investigation of albendazole, we focused on evaluating the dissolution rate of albendazole solid dispersion and its physical mixture in simulated gastric fluid.…”
Section: Resultsmentioning
confidence: 99%
“…These factors play a role in charge distribution, solubility, aggregation, and hydrophobicity, which are key to skin permeability and antimicrobial efficacy. Some AMPs exhibit optimal activity within specific pH or ionic strength ranges …”
Section: Different Transdermal Delivery Methodsmentioning
confidence: 99%
“…Some AMPs exhibit optimal activity within specific pH or ionic strength ranges. 97 Despite its significant potential, the transdermal delivery of AMPs using iontophoresis faces challenges. Potential skin irritation or damage caused by electric currents or electrodes requires careful attention and proper control.…”
Section: Iontophoresismentioning
confidence: 99%
“…NaCl and KCl are some salts that are used in dissolution media to mimic biological fluids under fed and fasted conditions. Nashed et al conducted experiments with various KCl concentrations and found that solubility was improved by alkaline ions like potassium, which led to an increase in the release rate (10). Also, increasing the ionic strength beyond a certain point eventually resulted in decreased dissolution efficiency by indicating the salting out of the polymer by the organic ions in the media, prolonging the drug release (10).…”
Section: Ionic Strengthmentioning
confidence: 99%